Ask a Question

Feed

Asked on 26/06/2017 Factorization

how i make a best actor

Answer

Answered on 20/11/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

Muraleedharan R

Tutor

= n (m + p) + q (m +p) = (m + p) ( n + q)

Like 1

Answers 6 Comments Answered on 22/11/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

Find the value of x6 + 1 / x6, if x + 1 / x?

Ankit Agarwal

Quest for education

2.

Like 0

Answers 1 Comments Answered on 03/12/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

If 4x - 4x - 1 = 24 then (2x)x equals what?

Dinnu Dexter

Not defined

Like 0

Answers 1 Comments Answered on 07/12/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

Factorise: (cube of x) + x - 3 (square of x) - 3?

Shambhavi S.

x^3-3x^2+x-3 is the given equation. Taking x^2 as common from the first two terms, we get, x^2(x-3)+1(x-3) , which can be written as, (x^2+1)(x-3). Thus (x^2+1) and (x-3) are the factors of the equation.

Like 0

Answers 1 Comments Answered on 22/11/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

Simplify: a9 - 64a3 - a6 + 64?

Shikha Yadav

Tutor

Please see the attachment for full solution. Final factors are (a3-1) (a3-8) (a3+8).

Like 0

Answers 1 Comments Answered on 07/12/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

Prove that: (1 / a3) + (1 / b3) + (1 / c3) = (1 / a + 1 / b + 1/c)3 + 3 / abc?

Shambhavi S.

we know that, a3 + b3 + c3 = (a + b + c)3 -- 3(a + b)(b + c)(c + a) a + b + c = 0 implies a + b = -- c, b + c = -- a, c + a = -- b. (1/a)3 + (1/b)3 + (1/c)3 = (1/a + 1/b + 1/c)3 -- 3(1/a + 1/b)(1/b + 1/c)(1/c + 1/a) = (1/a + 1/b + 1/c)3 -- 3(a+b / ab)(b + c / bc)(c + a / ac) = (1/a + 1/b + 1/c)3 --... read more

we know that, a3 + b3 + c3 = (a + b + c)3 – 3(a + b)(b + c)(c + a) a + b + c = 0 implies a + b = – c, b + c = – a, c + a = – b. (1/a)3 + (1/b)3 + (1/c)3 = (1/a + 1/b + 1/c)3 – 3(1/a + 1/b)(1/b + 1/c)(1/c + 1/a) = (1/a + 1/b + 1/c)3 – 3(a+b / ab)(b + c / bc)(c + a / ac) = (1/a + 1/b + 1/c)3 – 3(– c / ab)(– a / bc)(– b / ac) = (1/a + 1/b + 1/c)3 – 3(abc / a2b2c2) = (1/a + 1/b + 1/c)3 – 3 / abc. Thus, proved. read less

Like 0

Answers 1 Comments Answered on 22/11/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

What do you mean by factorization?

Chandan Singh

Tutor

Factorisation:- The resolution of an entity into factors such that when multiplied together they give the original entity.

Like 0

Answers 1 Comments Asked on 09/11/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

What is the value x + 1 / x, if x3 + 1 / x3?

Answer

Asked on 09/11/2016 Tuition/Class IX-X Tuition Tuition/Class IX-X Tuition/Mathematics Factorization

Factorize: (3 * a * x) - 2 . b . x + 3 . a. y - 2 . b. y?

Answer

UrbanPro.com helps you to connect with the best in India. Post Your Requirement today and get connected.

x

Ask a Question